Global Monitoring Report 2004 : Policies and Actions for Achieving the Millennium Development Goals and Related Outcomes - IMF; World Bank (Global Monitoring Report, 2004)
The turn of the century was marked by some significant and promising events for world development. The Millennium Declaration - signed by 189 countries in September 2000 - led to the adoption of the Millennium Development Goals, which set clear targets for eradicating poverty and other sources of human deprivation. Following other major international meetings came broad agreement on the goals and strategies to achieve them. The task now is implementation - to translate vision into action. Drawing attention to priorities for action and related accountabilities, the new Global Monitoring Report provides an integrated assessment of the policies and actions needed to achieve the Millennium Development Goals. Produced in cooperation with the International Monetary Fund (IMF) and other international partners, the Report assesses how the various parties-developing countries, developed countries, and international financial institutions-are playing their part under the agreed development partnership and highlights progress on the development policy agenda